Event-Based Resilient Control of Multi-Agent Systems in Non-Ideal Communication Networks - Lyu, Jianting; Sun, Lianghui; Wang, Xin; Gao, Dai (Frontiers in Control Engineering, 2022)
This article focus on the consensus problem of linear multi-agent systems under denial-of-service attacks and switching directed topologies. With only intermittent communication, the leader-following consensus can be preserved by a fully distributed event-triggered strategies. Theoretical analysis shows that the proposed event-triggered resilient controller guarantees the exponential convergence in the presence of denial-of-service attacks, and the exclusion of Zeno behavior. Compared to the existing studies where con- tinuous communication and control are required, the event-triggered data reduction scheme is provided to tackle the effects of denial-of-service attacks on directed switching topology, as well as to avoid continuous communication and reduce energy consumption. The obtained results can be extended in the scenario without a leader. Numerical simulations are finally given to illustrate the effectiveness of the proposed method.